The natural course of hepatitis C virus infection 18 years after an epidemic outbreak of non-A, non-B hepatitis in a plasmapheresis centre. Issue 4 (1st April 1999) - Datz, C; Cramp, M; Haas, T; Dietze, O; Nitschko, H; Froesner, G; Muss, N; Sandhofer, F; Vogel, W
Abstract : BACKGROUND: The natural history of hepatitis C virus (HCV) infection is variable and factors determining the course of the illness are unclear. AIMS: To determine the natural course of HCV infection in a well characterised group of patients 18 years after an epidemic outbreak of non-A, non-B hepatitis at a plasmapheresis centre. METHODS: Between 1994 and 1996, 20 of 30 affected individuals were studied. HCV infection was confirmed using second and third generation ELISA test kits. HCV RNA was detected by a polymerase chain reaction (PCR) method and HCV genotyping was performed by analysing amplicons from the conserved 5′-non-translated region generated by nested PCR. Thirty two liver biopsies were carried out in 14 patients. RESULTS: HCV antibodies were detected in all subjects. Eighteen patients had abnormal liver enzymes and 17 were HCV RNA positive, all of whom were infected with genotype 1a. Ninety per cent of this cohort showed evidence of chronic HCV infection with 50% having progressive liver disease and 20% cirrhosis 18 years after acute onset of non-A, non-B hepatitis. Considerable variation in disease outcome occurred between individuals and no correlation with clinical features of the acute illness was found. CONCLUSIONS: Variability in the consequences of HCV infection in cases infected with the same virus suggests that host factors are important in determining disease outcome. The factors which determine differences in the natural history of the disease still remain to be elucidated.